Tecituras na atividade docente: no fio da meada o ethos emana as renormalizações e dramáticas do corpo-si - Santos, Tanise Corrêa dos (2017)
This research, Tecituras na atividadedocente: no fio da meada o ethos emana as renormalizações e dramáticas do corpo-si, aims to analyze the scenography and the discursive ethos intertwined and imbricated in the teaching activity, as well as the discursive marks inferred from the renormatizations and the dramatic use of self to uncover how the denneutralization occurs with the educational environment. We are anchored in the conceptions of Yves Schwartz (2010a, 2011, 2014), Schwartz and Durrive (2010), Nouroudine (2002), and Souza e Silva (2002, 2008), as for ergology. In addition, the theoretical assumptions of Dominique Maingueneau (2008a, 2008b, 2010, 2015) about Global Semantics – scenography and discursive ethos are allied to this study. This study is justified considering the new education parameters implemented in the year 2012 at High Schools of the State of Rio Grande do Sul which are now belonging to the Polytechnic System. This research was based on a Polytechnic School located in the countryside of Santo Ângelo - RS belonging to the 14ª Coordenadoria Regional de Educação de Santo Ângelo/RS. These regimental beacons must be observed along with the self image of the educators that operationalize this system, against teaching work, the contemporary universe, the teaching profession – as to public education. Thus, the teaching action is often redesigned based on the commitment to the educational work which provides pedagogical support for talking and tweaking professional choices. From the foundation of the constitutive plans of discourse, the scenography of the teaching discourses are based on the uncertainties of the educational world, in addition, teacher knowledge is (re)shaped by the work of experience, thus the éthe reveal themselves to be workers, servile, solicitors, persevering, but at the same time they are concerned with education. Therefore we have an ethos committed to an educational and conservative work in relation to education